A Review and Clarification of the Terms “holistic,” “configural,” and “relational” in the Face Perception Literature - Piepers, Daniel; Robbins, Rachel (Frontiers in Psychology, 2012)
It is widely agreed that the human face is processed differently from other objects. However there is a lack of consensus on what is meant by a wide array of terms used to describe this “special” face processing (e.g. holistic and configural) and the perceptually relevant information within a face (e.g. relational properties and configuration). This paper will review existing models of holistic/configural processing, discuss how they differ from one another conceptually and review the wide variety of measures used to tap into these concepts. In general we favour a model where holistic processing of a face includes some or all of the inter-relations between features and has separate coding for features. However, some aspects of the model remain unclear. We propose the use of moving faces as a way of clarifying what types of information are included in the holistic representation of a face.